2007
DOI: 10.1007/s00586-007-0311-4
|View full text |Cite
|
Sign up to set email alerts
|

Metal levels in corrosion of spinal implants

Abstract: Corrosion affects spinal instrumentations and may cause local and systemic complications. Diagnosis of corrosion is difficult, and nowadays it is performed almost exclusively by the examination of retrieved instrumentations. We conducted this study to determine whether it is possible to detect corrosion by measuring metal levels on patients with posterior instrumented spinal fusion. Eleven asymptomatic patients, with radiological signs of corrosion of their stainless steel spinal instrumentations, were studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Kim et al [18] measured serum levels of nickel and chromium after posterior spinal arthrodesis using stainless steel implants and found that levels diminish rapidly with time but remained above normal levels after surgery suggesting that ion levels decrease as fusion occurred. A study by del Rio et al [19] described similarly elevated serum nickel and chromium levels in patients with instrumented spinal arthrodesis, noting the correlation between significantly higher metal ion levels and radiological signs of device corrosion. Rackham et al [21] determined that the number of metal connections/interfaces was positively correlated with serum chromium levels in a group of 30 patients undergoing posterior spinal arthrodesis.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Kim et al [18] measured serum levels of nickel and chromium after posterior spinal arthrodesis using stainless steel implants and found that levels diminish rapidly with time but remained above normal levels after surgery suggesting that ion levels decrease as fusion occurred. A study by del Rio et al [19] described similarly elevated serum nickel and chromium levels in patients with instrumented spinal arthrodesis, noting the correlation between significantly higher metal ion levels and radiological signs of device corrosion. Rackham et al [21] determined that the number of metal connections/interfaces was positively correlated with serum chromium levels in a group of 30 patients undergoing posterior spinal arthrodesis.…”
Section: Introductionmentioning
confidence: 90%
“…Studies of metal ion levels in patients with spinal implants are less numerous. There have been only a few retrospective reports of metal ion levels in patients with stainless steel [18][19][20][21][22] and titanium [23,24] posterior spinal instrumentation. Less is known for metalon-metal total disc arthroplasty [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with spinal instrumentations, retrieved and characterized by signs of corrosion, even if without radiological symptoms, increased levels of chromium in serum and urine were present, compared with volunteers without implants 20…”
Section: Discussionmentioning
confidence: 95%
“…Higher Ni and Cr levels were found in subjects with corrosion of stainless steel posterior instrumented spinal fusion, in comparison with stable patients and controls 20…”
Section: Introductionmentioning
confidence: 82%
“…For Ni-based restorative alloys, patients undergoing Ni–Cr replacement 1 year ago had a higher level of serum Ni than that of controls. 15 Other Ni-based implants have also demonstrated significantly increased Ni concentrations in body fluids after the implantation, such as hip prostheses, 29 cardiac device, 30 spinal instrumentation 31 and tungsten alloy. 32 …”
Section: Discussionmentioning
confidence: 99%